Advanced Oxidation Processes as sustainable technologies for the reduction of elderberry agro-industrial water impact - L.C. Ferreira; I. Salmerón; J.A. Peres; P.B. Tavares; M.S. Lucas; S. Malato (Water Resources and Industry, 2020)
World is facing an environmental crisis and industrial awareness regarding their wastewaters is gaining strength. By treating them, water footprint can be reduced allowing their recycle and reuse, as well as recovering substances with added value. This work reports the pre-treatment of non-biodegradable elderberry agro-industrial wastewater at pilot plant scale by different oxidative processes (solar photo-Fenton, solar electrochemistry and ozonation). An economical approach has been addressed for improving biodegradability for a subsequent lower-cost biological treatment. Solar photo-Fenton process attained biodegradability in 30 min entailing 0.22 € m−3 of operation costs. Solar photoelectro-Fenton treatment turned industrial wastewater biodegradable after 20 min costing 0.11 € m−3, while solar-assisted anodic oxidation required 60 min and 0.12 € m−3. Solar processes combined with electrooxidation showed to be more promising options than ozonation for reducing water footprint of biorecalcitrant industrial wastewaters and moderate organic content, if an engagement between treatment time and operating costs is prioritized.